THE THREE DIMENSIONS OF INTENTIONALITY - Krokos, Jan (Studia Philosophiae Christianae, 2020)
The issue of intentionality was posed anew in philosophy by Franz Brentano. However, it was Brentano himself who indicated that the source of intentionality-related problems dates back to Classical Antiquity and the Middle Ages. The search for the original traces of this issue in the history of philosophy has led me to conclude that intentionality as an inalienable characteristic of consciousness is characterized by three-dimensionality, which is expressed in theoria, praxis and poiesis. Contemporary research focuses primarily on cognitive intentionality, examining in particular either the very subject-object relation or the immanent (intentional) object, in-existing in psychical experience (in the acts of consciousness). And yet, intentionality is a basic feature of the whole consciousness-anchored (mental) life of a human being. It determines the whole consciousness-based activity of the subject in abstract theorizing, practice and production. Therefore, it manifests itself as a mode of being of a conscious (mental) entity, i.e. an entity partially constituted by intentional content, relationality, reference, directionality, openness and conscious awareness , as well as determining the meaning and the creation of purely intentional beings. Intentionality is revealed as a primary factor in the awakening of consciousness, through the building (constituting) of conscious experiences that are poietic, practical and theoretical. Each of these three ways of categorizing the nature of experience, however, indicates only the predominant aspect of a given experience, for strictly speaking experiences are determined by all three aspects. Intentionality and – consequently – all conscious experience, are thus characterized by three-dimensions: cognitive, activistic and productive. Any act of consciousness is always a form of activity that is informed by its cognitive aspect and produces something transcendent with regard to itself. The recognition of the three-dimensional nature of intentionality allows us to understand the human being and the dilemmas concerning his actions, knowledge and creativity.